Taste-Masked Flucloxacillin Powder Part 2: Formulation Optimisation Using the Mixture Design Approach and Storage Stability - Okhee Yoo; Sam Salman; Britta S. von Ungern-Sternberg; Lee Yong Lim (Pharmaceuticals, 2023)
Flucloxacillin is prescribed to treat skin infections but its highly bitter taste is poorly tolerated in children. This work describes the application of the D-optimal mixture experimental design to identify the optimal component ratio of flucloxacillin, Eudragit EPO and palmitic acid to prepare flucloxacillin taste-masked microparticles that would be stable to storage and would inhibit flucloxacillin release in the oral cavity while facilitating the total release of the flucloxacillin load in the lower gastrointestinal tract (GIT). The model predicted ratio was found to be very close to the stoichiometric equimolar component ratio, which supported our hypothesis that the ionic interactions among flucloxacillin, Eudragit EPO and palmitic acid underscore the polyelectrolyte complex formation in the flucloxacillin taste-masked microparticles. The excipient–drug interactions showed protective effects on the microparticle storage stability and minimised flucloxacillin release at 2 min in dissolution medium. These interactions had less influence on flucloxacillin release in the dissolution medium at 60 min. Storage temperature and relative humidity significantly affected the chemical stability of the microparticles. At the preferred storage conditions of ambient temperature under reduced RH of 23%, over 90% of the baseline drug load was retained in the microparticles at 12 months of storage.